Dexmedetomidine Alleviates Intracerebral Hemorrhage-Induced Anxiety-Like Behaviors in Mice Through the Inhibition of TRPV4 Opening - An, Ping; Zhao, Xiao-Chun; Liu, Man-Jia; You, Yu-Qing; Li, Jing-Ya; Gong, He-Song (Frontiers in Pharmacology, 2022)
Post-stroke anxiety severely affects recovery in patients with intracerebral hemorrhage (ICH). Dexmedetomidine (Dex), a highly selective alpha 2 adrenal receptor (α2-AR) agonist, was recently found to exert an excellent protective effect against mental disorders including anxiety. The transient receptor potential vanilloid 4 (TRPV4) channel is involved in a series of diseases such as asthma, cancer, anxiety, and cardiac hypertrophy. This study examines whether Dex improved ICH-induced anxiety via the inhibition of TRPV4 channel opening. A rodent model of moderate ICH in the basal ganglia was established using autologous blood injection (20 μl). Mice were treated with Dex (25 μg/kg, intraperitoneal injection) every day for 3 days post-ICH. GSK1016790A (1 μmol/2 μl), an agonist of TRPV4, was administered via the left lateral ventricle. Thirty days post-ICH, post-stroke anxiety was evaluated by elevated plus-maze and open-field tests. Following behavioral tests, superoxide dismutase (SOD), malondialdehyde (MDA), astrocytic activation, and A1-and A2-type astrocytes were determined. Primary astrocytes were exposed to hemin to simulate ICH in vitro. Compared with sham-treated mice, Dex administration ameliorates ICH-induced decreases of distance and time in the open-arm, reduces distance and time in the central zone, increases astrocytic activation and A1-type astrocytes, elevates MDA content, downregulates total SOD contents, and decreases A2-type astrocytes. However, GSK1016790A partially reversed the neuroprotective effects of Dex. In addition, Dex significantly inhibited hemin-induced astrocytic activation in vitro. Dex improves ICH-induced anxiety-like behaviors in mice, and the mechanism might be associated with the inhibition of TRPV4-channel opening.